New species and subspecies of Babiana, Hesperantha, and Ixia (Iridaceae: Crocoideae) from southern Africa; range extensions and morphological and nomenclatural notes on Babiana and Geissorhiza - P. Goldblatt; J. C. Manning (Bothalia: African Biodiversity & Conservation, 2012)
Babiana rivulicola from stream banks in the Kamiesberg in Namaqualand and terete-leaved Ixia teretifolia from the Roggeveld, both in Northern Cape, are new species of these two largely winter-rainfall region genera. Late-flowering populations of Hesperantha radiata with crowded spikes of smaller flowers are segregated from the typical form as subsp. caricina. We also document the first record of B. gariepensis from Namibia, correct the authority for B. purpurea Ker Gawl., discuss morphologically aberrant populations of B. tubiflora from Saldanha, provide an expanded description for B. lapeirousiodes based on the second and only precisely localized collection of this rare Namaqualand species, and expand the circumscription of Geissorhiza demissa to accommodate a new record from the Kamiesberg, including revised couplets to the existing key to the species.